Structural failure simulation of onshore wind turbines impacted by strong winds. (1st May 2018) - Chou, Jui-Sheng; Ou, Yu-Chen; Lin, Kuan-Yu; Wang, Zhi-Jia
Highlights: This study investigates the causes of tower collapse to support the hazard-resistant design of future wind turbines. Comprehensive data are obtained to simulate wind turbine collapse. Turbine force scenarios and their finite element analyses are carried out to identify mechanisms of structural weakness planes. Improvement solutions on strong wind resistance of wind turbines and their benefits are discussed. This study gives recommendations on the blade-pitch system, reinforcement of tower structure, and weaker blades being a safety mechanism for the wind turbines. Abstract: The renewable energy industry is thriving in many countries against a global backdrop of growing environmental awareness. In particular, in Taiwan, wind is emerging as a potential source. The Taiwanese government has implemented the "Thousand Wind Turbines" project as a collaboration with the private sector to construct a wind power infrastructure. However, when Typhoon Soudelor hit Taiwan on August 7–8, 2015, the towers of 2.0 MW wind turbines close to Taichung harbor collapsed and falling blades damaged one of the collapsed turbine towers. This incident of wind turbine collapse was the second in the nation and was more extensive than the previous one. This study investigates the causes of this incident and the mechanical mechanisms of turbine tower collapse and blade fracture to support risk prevention and hazard-resistant design of future wind turbines. Relevant data are obtained to simulate wind turbine collapse. Next, mechanical analyses via finite element method are carried out to identify mechanisms of failure and structural weakness planes, with the ultimate purpose of summarizing potential causes of collapse. Improvement solutions on strong wind resistance of wind turbine towers and their benefits are discussed. Finally, this study gives the recommendations on weaker blades being a safety mechanism for the wind turbine tower, torque capacity of the pitch system as well as the required strength of joint bolts to be installed in steel structural connections, so as to withstand severe storms.